Gendered Patterns of Conscious Consumption: Exploring Moderation Effects in Consumer Decision-Making Behavior - April, Dian; Purwoko, Purwoko; Setiawan , Zunan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
In the evolving landscape of consumer behavior, decision-making is increasingly shaped by multifaceted psychological constructs. This study investigates the influence of five key dimensions of consumer consciousness fashion consciousness, brand consciousness, price consciousness, quality consciousness, and confusion by over choice on consumer purchase decision-making (CPDM), while exploring the moderating role of gender. Using Partial Least Squares Structural Equation Modeling (PLS-SEM 4.0), data were analyzed to reveal how each latent variable contributes uniquely to shaping consumer behavior in a saturated marketplace. The findings show that while gender does not significantly moderate the effects of fashion or price consciousness on CPDM, it does influence the impact of brand consciousness and confusion by over choice. Specifically, men tend to respond more strongly to brand cues, while women are more susceptible to decision fatigue caused by excessive choices. These results underscore the nuanced role of gender as a psychological filter in consumer decision-making processes. This research contributes to a deeper understanding of behavioral segmentation and offers practical implications for marketers aiming to design more gender-sensitive strategies in increasingly crowded consumer markets.